UJI ADAPTIF BEBERAPA VARIETAS KEDELAI (Glycine Max (L) Merril) PADA AGROEKOSISTEM LAHAN KERING SPESIFIK LOKASI PADA MUSIM TANAM JUNI DI KEBUN PERCOBAAN LAMPINEUNG NANGGROE ACEH DARUSSALAM - Burlis Han (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2006)
Adaptive Test of Some Soybean Varieties (Glycine Max (L) Merril) At Specific Dry Land Agroecosystem on Planting Season of June in Lampineung Experimental Station, Nanggroe Aceh Darussalam Burlis Han ABSTRACT A research of the adaptive test of some soybean varieties at specific agroecosystem of specific dry land location has been conducted in Experimental Station of Lampineung Banda Aceh at plant season of 28 June 2004. Production of Soybean on dry land in Province of Nanggroe Aceh Darussalam (NAD) is still low and its productivity increase moves tardy. From 1989 - 1994 the soybean production was successively: 1,6 ; 1,18 ; 1,18 ; 1,20 and 1,21 tons/ha. Some constraints often met in dry land soybean cultivation are low and varied land fertility, high weed population, low seed quality and unestimated rainfall pattern. Especially for seed, constraint faced by farmer in production center area is unavailability of superior seed. This research was aimed to get superior varieties of Soybean which is adaptive in specific location. This research started from June to September 2004. This research used Non Factorial Randomized Complete Block Design, followed by Duncant Multiple Rank Test. Treatment factors were five varieties of Soybean, consisting of Kaba, Merbabu, Mahameru, Sinabung and Pangrango. Observation of adaptability was based on variablity of growth and production component. Results of research showed that average production which can be reached were Kaba 1.202,5 kgs/ha, Mahameru 652,5 kgs/ha, Merbabu 1.787,5 kgs/ha, Pangrango 1.219 kgs/ha and Sinabung 1.660,6 kgs/ha. The most adaptive variety are Merbabu and Sinabung.